The Relationship of Time Management with The Habit of Academic Procrastination in Nursing Students - Khotimah, Khusnul; Suratmi, Suratmi; Qowi, Nurul Hikmatul (Journal of Nursing and Midwifery Sciences, 2022)
Introduction: Students have many tasks, especially in nursing students but not a few students who often delay doing tasks. This is called the habit of academic procrastination. An important factor or triggers the habit of academic procrastination, one of which is time management. This research aims to analyze the relationship of time management with academic procrastination habits in nursing students. Method: This study uses analytic correlation design. The sample was taken with a simple random sampling technique that is as many as 110 respondents. Data collected from respondents using questionnaire sheets, then tested using spearman rho test. Results: The results showed that 77 students (70%) had adequate time management. Student prokrastization is in the moderate range, which is 72 students (65.5%). Spearman Rho test obtained a value of P = 0.000, so it can be concluded that there is a relationship between time management and the academic procrastination habits of nursing students. Conclusions: A good timing management such as preparing to make a list of everything that will be done which is arranged according to their level of importance, arrange activities to be carried out so that they are self-disciplined, determine task priorities according to their vital level of importance, arrange what is being done today and tomorrow will have an impact on the low habit of academic procrastination. Student can practice to do time management well, so that students can achieve good academic goals with many extracurricular activities